Development of Test Instruments to Identify Student Misconceptions Using Digital Theree-Tier Diagnostic Test on Direct Current Materials - Mirna*, Salmiah Sari, Helmi (Journal of Physics Education : Review and Research, 2024)
Development of Test Instruments to Identify Students' Misconceptions using the Digital Three-Tier Diagnostic Test on Direct Current Material. This study aims to determine the validity and reliability of the test instrument developed so that it can be used to identify students' misconceptions on direct current material for class XII SMA. To find out the objectives, the content validity coefficient, reliability coefficient of instrument items have been obtained. The subjects of this study were students of class XII IPA SMAN 4 Barru which consisted of 38 people. Data collection techniques used are tests and expert assessment validation sheets. The instrument used is a three-tier diagnostic test instrument. The steps for developing a three-tier diagnostic test instrument are compiling test specifications, writing questions, reviewing questions, conducting trials, analyzing items, improving items and assembling test items. The number of items developed was 40 items of three-level multiple choice questions. The number of items tested were 25 items. The results of the calculation of the validity of the internal consistency coefficient value obtained by r = 0.88. The instrument was tested twice and produced a reliability coefficient of 0.86 for the first test and 0.82 for the second test. With the results of the analysis that has been obtained, the test instrument developed is classified as valid and reliable both theoretically and empirically.